Association between Frequency of Breakfast Eating and Obesity in Korean Adolescents - Jong-Hyuck Kim; Wi-Young So (Tehran University of Medical Sciences, 2012)
Background: The purpose of this study was to examine whether the frequency of breakfast eating was related with overweight/obesity in Korean adolescents.Method: We analyzed the data collected in the 5th KYRBWS, in which 72,399 adolescents participated in 2009. We assessed the association between frequency of breakfast eating and body mass index by using multivariate logistic regression analysis.Results: A total of 20,962(54.9%) boys and 18,479(54.0%) girls skipped breakfast 7 days(all days) per week at baseline. For boys, the odds ratios(ORs) between being overweight and frequency of breakfast eating were 1.040 for 3-5 times per week, 1.092 for 1-2 time(s) per week, 1.059 for no breakfast per week, compared to 6-7 times per week(p>0.05). The ORs between being obese and frequency of breakfast eating were 1.011 for 3-5 times per week, 0.968 for 1-2 time(s) per week, and 0.932 for no breakfast per week, compared to 6-7 times per week(p>0.05). For girls, the ORs between being overweight and frequency of breakfast eating were 0.990 for 3-5 times per week, 0.992 for 1-2 time(s) per week, 1.019 for no breakfast per week, compared to 6-7 times per week(p>0.05). The ORs between being obese and frequency of breakfast eating were 1.075 for 3-5 times per week, 0.946 for 1-2 time(s) per week, and 0.941 for no breakfast per week, compared to 6-7 times per week(p>0.05).Conclusion: The frequency of breakfast eating has no correlation with overweight/obesity in Korean adolescents.